Social Intelligence and Counselling Competencies of Prospective Counsellors in Public Universities in Nigeria - Omogbai, Edith Omorionmwen; Martins, Igbineweka Noyosase (International Journal of Applied Guidance and Counseling, 2024)
This study investigated the social intelligence and counselling competencies of prospective counsellors and the difference in sexes in Public Universities in Edo and the Delta States of Nigeria. To achieve the objectives, three research questions were raised and one corresponding hypothesis was formulated and tested at a 0.05 level of significance. A survey research design adopting the correlational approach was employed in the study. The population of the study comprised all master's students in public universities in Edo and Delta States in the 2017/2018 and 2018/2019 sessions who had completed practicum counselling courses. A sample of 89 prospective counsellors was used for the study. The researcher used two types of instruments to collect data, practicum scores were one of the data for this study. The instruments used are the Tromso Social Intelligence Scale (TSIS), and the Counsellors Competency Scale (CCS). The instruments were validated by the researcher’s supervisors and one test expert in the Department of Educational Evaluation and Counselling Psychology. The reliabilities of the instruments were established, using the Cronbach alpha statistics. A reliability coefficient of 0.84 was obtained for the Social Intelligence scale. Coefficients of 0.81, 0.90, and 0.80 were obtained for knowledge, skills and behavioural sub-scales for the Counsellor Competency Questionnaire. Data analyses were carried out and the hypothesis was tested using Fisher’s-Z test statistics. The study's findings revealed no significant difference in the relationship between social intelligence and counselling competencies of prospective counsellors by sex in public universities in Edo and Delta States.